2023
DOI: 10.1182/bloodadvances.2022008989
|View full text |Cite
|
Sign up to set email alerts
|

Reduced FVIII recovery associated with anti-FVIII PEG antibodies after BNT162b2 SARS-CoV-2 vaccination

Abstract: Prophylactic therapy has become the standard of care for patients with hemophilia A (HA); however, prophylaxis regimens that require 2 to 3 weekly infusions of drug are challenging. In the past decade, new factor VIII (FVIII) molecules with extended plasma half-life have been produced with the goal of reducing the number of infusions while maintaining higher trough levels of FVIII in plasma. [1][2][3][4] One of the most established approaches to prolong the circulation time while preserving the biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Both in this report and N8‐GP clinical trials, some patients with haemophilia A had anti‐PEG antibodies prior to N8‐GP exposure. Studies have shown that exposure to PEG molecules through medication and consumer products is widespread in the general population (e.g., packaged foods, paracetamol, COVID‐19 vaccines) 16–18 . COVID‐19 lipid nanoparticle mRNA vaccines contain small amounts of PEG, which have been shown to induce anti‐PEG antibodies in some individuals 19 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both in this report and N8‐GP clinical trials, some patients with haemophilia A had anti‐PEG antibodies prior to N8‐GP exposure. Studies have shown that exposure to PEG molecules through medication and consumer products is widespread in the general population (e.g., packaged foods, paracetamol, COVID‐19 vaccines) 16–18 . COVID‐19 lipid nanoparticle mRNA vaccines contain small amounts of PEG, which have been shown to induce anti‐PEG antibodies in some individuals 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exposure to PEG molecules through medication and consumer products is widespread in the general population (e.g., packaged foods, paracetamol, COVID-19 vaccines). [16][17][18] COVID-19 lipid nanoparticle mRNA vaccines contain small amounts of PEG, which have been shown to induce anti-PEG antibodies in some individuals. 19 It is currently unknown how transient the anti-PEG antibody response is, and whether the concentration of the induced anti-PEG antibodies can affect the exposure of PEGylated medicines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations